Performance.corpo.contexto: trajetos entre arte e desejo - Nascimento, Ana Reis (2011)
This dissertation is supported by the possibility of conceiving reading as a performance at minimum degree, turning language into a metalinguistic or metaperformative exercise that tries to activate the reader s body through investigating performance, body and the context of its accomplishment. Permeating contemporary art paradigms and the political/social/cultural context of the mediatized industrial capitalistic society, we find evidences of desire insolvencies and potencies that, when investigated on their productive features, cross and allow themselves to be crossed by subjectivities and their collective assemblages. Reports on one performance are recreated and revived in order to reflect on the discussed concepts considering the relationship of the performance with space, time, form, receptions and codes that permeate and constitute it. We compose a territory that is unfolded in multiple slopes: from concept to accomplishment, from the theoretical foundation to the reflection embedded and/or embodied in it, from conceptual landscape to the specificities of experience.